Cash Waqf According to the Views of Four Madzhabs (Study of the Book Al-Fiqh Al-Islami Wa Adillatuhu) - Ulum, Bahrul (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
As science and technology develop, so does a nation's economy, and so does the way in which Shari'ah is implemented for Muslims, including in the case of waqf. Previously, waqf was limited to the use of permanent objects such as land, buildings and so on, so now waqf is being introduced in the form of money. This situation is certainly a new breakthrough, which often gives rise to resistance among fiqh scholars. The aim of this research is to find out about the law of cash waqf from the perspective of four schools of thought according to the book of Islamic jurisprudence wa adillatuhu with the hope that it will provide more complete information about the law of cash waqf and bring peace to Muslims. The research method used is qualitative. This research approach uses descriptive analysis of primary data, namely the book of Islamic jurisprudence wa adillatuhu written by Syeh Wahbah Az-Zuhaili. The findings of this research conclude that waqf in the form of money is legal because waqf in the form of dinars and dirhams is permissible. Cash waqf is permissible because there are verses and hadiths that strengthen cash waqf. Moreover, with the increasing pace of civilisation, cash waqf is very easy to distribute, such as through bank transfers in remote areas. Most ulama in the millennial era agree that cash waqf is permissible and legal, provided the procedures are understood.